Makna Simbolik Tradisi Megengan Bagi Warga Desa Ngadirojo Ponorogo - Medina M, Avriliani Virliya (Paradigma, 2022)
This paper discusses the symbolic meaning of the megengan tradition for the villagers of Ngadirojo Ponorogo. Megengan is a tradition that is carried out before carrying out the fasting month by Javanese residents. In the implementation of this modern era, Ngadirojo village residents still use complete and incomplete offerings. The symbolic meaning of the megengan tradition for the villagers of Ngadirojo Ponorogo can be analyzed using the symbolic interactionism theory of Herbert Blumer. The purpose of this study was to determine the symbolic meaning of the megengan tradition for the villagers of Ngadirojo Ponorogo. This study uses a qualitative method with a phenomenological approach. The location of the research was conducted in Ponorogo, precisely in Ngadirojo village, Sooko sub-district. The research subjects came from Ngadirojo village residents who still carried out megengan complete with ritual offerings aged between 60-80 years for the elderly and 30-40 years for millennials. The results of the study show that the residents of Ngadirojo village still carry out megengan every year, both using and not using offerings. The symbolic meaning of foods in the megengan tradition such as mule, dry tofu tempeh, vegetable lodeh, srondeng, apem cake, red jenang, sengkala jenang, golong rice, strong buceng rice, roasted chicken apostles are various. Each food has a symbolic meaning that is used as a means of interacting with God using the teachings of previous ancestors. There is a complete meaning of the megengan tradition of using offerings for individuals as respect for ancestors, social integration, social harmony, awareness of worship and means of salvation. There is also a meaning based on the exchange of symbols attached to the individual which shows the various variations of megengan that exist in Ngadirojo village. Keywords: Symbolic Meaning, Megengan, Tradition